CONTRIBUCION AL ESTUDIO DE LAS ALTERACIONES CELULARES HEPATICAS CONSECUTIVAS A LA LIGADURA DEL COLEDOCO - VELEZ OROZCO, A C; VARGAS DE LA CRUZ, J; GONZALEZ GUZMAN, IGNACIO (Instituto de Salubridad y Enfermedades Tropicales, CD MEXICO, DF, MEX, 1947)
Donkey's milk lysozyme increases the bacteriolytical activity of human and animal sera In concn of 200 U and in standard conditions lysozyme does not lyse Staphylococcus aureus Proteus morgani Proteus X-19 Salmonella typhi S poona, S enteritidis and
BOL INST ESTUD MED BIOL
Keywords: CONTRIBUCION, ESTUDIO, ALTERACIONES, CELULARES, HEPATICAS, CONSECUTIVAS, LIGADURA, COLEDOCO; CIENCIAS MEDICAS; PATOLOGIA; ENFERMEDADES HEPATICAS